2012
DOI: 10.1002/prot.24050
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the TLDc domain of oxidation resistance protein 2 from zebrafish

Abstract: The oxidation resistance proteins (OXR) help to protect eukaryotes from reactive oxygen species. The sole C-terminal domain of the OXR, named TLDc is sufficient to perform this function. However, the mechanism by which oxidation resistance occurs is poorly understood. We present here the crystal structure of the TLDc domain of the oxidation resistance protein 2 from zebrafish. The structure was determined by X-ray crystallography to atomic resolution (0.97Å) and adopts an overall globular shape. Two antiparall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 24 publications
2
42
0
Order By: Relevance
“…The TLDc domain is coded by exons 19–24, which is indicated by a box in Figure . The TLDc domain is present in all eukaryotes and highly conserved among species (Blaise et al ., ). We compared the TLDc domain protein sequences of OXR1 among insects, nematode, mouse, human and yeast and found high similarity among the different species (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The TLDc domain is coded by exons 19–24, which is indicated by a box in Figure . The TLDc domain is present in all eukaryotes and highly conserved among species (Blaise et al ., ). We compared the TLDc domain protein sequences of OXR1 among insects, nematode, mouse, human and yeast and found high similarity among the different species (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The gene is expressed as several isoforms, all containing a C-terminal TLDc domain, which is highly conserved among species and present in all eukaryotes (Fig. 1 A) ( 53 , 54 ). The TLDc domain has also been shown to prevent oxidative damage in various organisms ( 51 , 52 , 55 ); however, its mechanism of action remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Using our unbiased proteomic approach, we have demonstrated for the first time that Oxr1 binds to proteins involved in the oxidative stress response. This is significant as it has been shown that Oxr1 plays an important role in these pathways, although the molecular mechanisms are unclear; particularly as the three-dimensional structure of the highly conserved TLDc domain did not reveal similarity to known antioxidant proteins ( 53 ). Thus, we investigated binding partners of both the longest (Oxr1-FL) and the shortest (Oxr1-C) TLDc-containing isoforms of Oxr1 for a comprehensive study.…”
Section: Discussionmentioning
confidence: 99%
“…We generated the structural model of human TBC1D24 with Phyre2, an online software, 21 based on the crystal structures of the TBC domain of TBC1D1 and TBC1D4 and the TBC, LysM, Domain catalytic (TLDc) domain of the zebrafish Oxr2 protein 22 . We made the three-dimentional figure using Pymol (version 1.6).…”
Section: Methodsmentioning
confidence: 99%